2007
DOI: 10.1029/2006jd008085
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of CMAQ‐based aerosol properties with IMPROVE, MODIS, and AERONET data

Abstract: [1] Evaluation of concentrations predicted by air quality models is needed to ensure that model results are compatible with observations. In this study aerosol properties derived from the Community Multiscale Air Quality (CMAQ) model-simulated aerosol mass concentrations are compared with routine data from NASA satellite-borne Moderate Resolution Imaging Spectroradiometer (MODIS) sensor aboard the Sun-synchronous Terra satellite, NASA's ground-based Aerosol Robotic Network (AERONET), and the ground-based Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 40 publications
4
49
0
2
Order By: Relevance
“…AOD from MODIS is retrieved separately over the ocean and land to account for differences in surface properties (e.g., Remer et al, 2005). While some studies have found a high AOD bias in the Western US due to the use of an estimated surface reflectance over the bright land surface , the SEUS has dense vegetation that provides good dark targets and greater confidence in the MODIS aerosol retrieval (Roy et al, 2007). For this work, we use Collection 5 Level 3 daily measurements and combine land and ocean optical depth retrievals.…”
Section: Satellite Observationsmentioning
confidence: 99%
“…AOD from MODIS is retrieved separately over the ocean and land to account for differences in surface properties (e.g., Remer et al, 2005). While some studies have found a high AOD bias in the Western US due to the use of an estimated surface reflectance over the bright land surface , the SEUS has dense vegetation that provides good dark targets and greater confidence in the MODIS aerosol retrieval (Roy et al, 2007). For this work, we use Collection 5 Level 3 daily measurements and combine land and ocean optical depth retrievals.…”
Section: Satellite Observationsmentioning
confidence: 99%
“…The variables evaluated column concentrations of tropospheric CO and NO 2 , tropospheric O 3 residual (TOR), and aerosol optical depth (AOD). To evaluate all observations related to MODIS, the monthly-mean AOD predictions are calculated as an average of column-integrated values during 15:00-20:00 UTC when the Terra satellite passes over Europe, following Roy et al (2007).…”
Section: Simulation Designmentioning
confidence: 99%
“…9d). Underestimations of CMAQ-derived AOT values have been reported by several authors before (Roy et al, 2007;Park et al, 2011).…”
Section: Study Of the Performance In Aot Predictionsmentioning
confidence: 99%
“…Many authors have looked into tometers that measures the optical properties of aerosols (Holben possible ways to use satellite or ground-based vertical observations of et al, 1998). The data obtained from AERONET consisted in the the atmosphere to assess air quality models such as CMAQ in a more daily average AOT level 2.0 at 440 nm (cloud-screened) for the consistent way (Roy et al, 2007). Although remote sensing data may entire month of July.…”
Section: Ground-level Observationsmentioning
confidence: 99%